Kualifikasi Justice Collaborator Dalam Perkara Tindak Pidana Korupsi (Studi Putusan Pengadilan Negeri Jakarta Pusat Nomor 48/Pid.Sus-TPK/2020/PN Jkt Pst) - Saliu, Abdul Rahman; Supusepa, Reimon; Fadillah, Astuti Nur (Pusat Kajian Korupsi Fakultas Hukum Universitas Pattimura, 2024)
Introduction: The law enforcement process has several stages, one of the most decisive in eradicating crime is the criminal justice system. There are several terms used in the judicial process, one of which is Justice Collaborator which is regulated in several regulations including Article 10 A paragraph (1) jo, paragraph 3 Law No. 31 of 2014 concerning PSK which in essence provides an explanation that